Securing nature’s contributions to people requires at least 20%–25% (semi-)natural habitat in human-modified landscapes - Mohamed, Awaz; DeClerck, Fabrice A.J.; Verburg, Peter H.; Obura, David; Abrams, Jesse F.; Zafra-Calvo, Noelia; Rocha, Juan; Estrada-Carmona, Natalia; Fremier, Alexander; Jones, Sarah K.; Meier, Ina C.; Stewart-Koster, Ben (Elsevier, 2024)
The cascading effects of biodiversity decline on human well-being present a pressing challenge for sustainable development. Conservation efforts often prioritize safeguarding specific species, habitats, or intact ecosystems but overlook biodiversity’s fundamental role in providing Nature’s Contributions to People (NCP) in human-modified landscapes. Here, we systematically review 154 peer-reviewed studies to estimate the minimum levels of (semi-)natural habitat quantity, quality, and spatial configuration needed in human-modified landscapes to secure functional integrity essential for sustaining NCP provision. We find that the provision of multiple NCP is threatened when (semi-)natural habitat in the landscape falls below an area of 20%–25% for each km2. Five NCP almost completely disappear below a level of 10% habitat. The exact quantity, quality, and spatial configuration of habitat required depends on local context and specific NCP. Today, about two-thirds of human-modified lands have insufficient (semi-)natural habitat, requiring action for NCP regeneration. Our findings serve as a generic guideline to target conservation actions outside natural areas.